Development of class 2 and class 3 surge protection devices for low voltage systems - Mohd Ariffen, Amizah (2011)
Due to the increased use of sensitive electronics, specifically microelectronics, even modest lightning activity can cause equipment indemnity. Lightning effects can Noccur at all levels of power systems either directly or indirectly, including transmission, generation, and distribution. Therefore, the use of surge protection can provide a solution to this problem. The International Electrotechnical Commission (IEC) and Institute of Electrical and Electronics Engineers (IEEE) introduced numerous international standards on the specified requirements and applications of low-voltage protection devices, for optimum and reliable protection. Currently, the ability of available surge protection devices is questionable, due to their poor design and unreliable protection of sensitive equipment. This project aims to study those requirement and application guidelines, with the purpose of designing, developing,and analysing, an adequate protective circuit for Class 3 and Class 2 categories. Computational (numerical analysis) and experimental methods have been applied, in addition to the analysis of previously designed devices, where their strengths and weaknesses have been compared. Next, improvements are proposed, based on the deficiencies of previous designs, which involved the coordination of different components to acquire a lower output voltage. The designed circuit will be simulated to achieve the best results, before PCB fabrication and high voltage laboratory testing. As a result, the output voltage of the Class 2 surge protection device is below 2000 V, and below 600 V for all protection modes of the Class 3 device. Therefore, Class 2 and Class 3 surge protection devices function effectively throughout the analysis and are capable of providing a dependable let-through voltage for end user application.